Contextualizing Accumulation by Dispossession: The State and High-Rise Apartment Clusters in Gangnam, Seoul. Issue 3 (3rd May 2020) - Sonn, Jung Won; Shin, Hyun Bang
Abstract : In an effort to contribute to the contemporary debates on accumulation by dispossession (ABD), we argue for a closer attention to the link between the state and ABD. We propose contextualizing ABD within the institutionalization of the process of replacing communal property rights with private property rights. In such institutionalization, the state plays a critical role as the final guarantor of property rights. As such, the sociospatial specificities of the state would strongly influence how ABD unfolds and how it is understood. In the empirical part of this article, we use this approach to focus on a specific type of capitalist state—that is, the developmental state—to examine the emergence of apartment-dominated residential landscapes in Gangnam District, Seoul, in the 1970s through the use of ABD. Key Words: accumulation by dispossession and primitive accumulation of capital, developmental state, Gangnam District, high-rise apartments, Seoul, South Korea, vertical accumulation .